Web-based learning solutions for communities of practice developing virtual environments for social and pedagogical advancement - Karacapilidis, Nikos (Advances in web-based learning series., 2010)
"This book provides readers with an up-to-date research manual in developing innovative and effective learning systems using web-based technologies"--Provided by publisher.